Enterprise modeling of a project-oriented fractal company for SMEs networking - Canavesio, Maria de Las Mercedes (2007)
To address competitive threats and concentrate in their core competences and strengths networking is the alternative of choice for survival and prosperity of most small and medium enterprises (SMEs) all over the world. For networking advantages to be fully grasped, an enterprise model describing the main organizational structure and relationships, information flows, management roles, actor behavior and constraints in the network is required. This work presents a conceptual model for SMEs networking based on the fractal company approach and concepts like projects, resources, goals, specialized actors, plans, and relationships thereof. The fractal company idea is a conceptual enterprise design that seeks to achieve a high degree of flexibility to react and adapt quickly to environmental changes using decentralized and autonomous organizational units known as fractals. In this work, each fractal management unit is modeled as a project. The fractal company is thus seen as a temporary set of client?server and delegation-to-do relationships among project-managers interacting so as to diversify product portfolio, gain economy of scale and share expensive costs. The proposed enterprise model can be used to specify the requirements of an integrated information and management system for virtual SMEs networking. The enterprise model is exemplified using a case study related to process development of a new pharmaceutical product in a SME network of the specialty chemical sector.